Pengaruh Kepuasan Kerja terhadap Disiplin Kerja Pegawai Kantor Camat Pangkalan Kerinci Kabupaten Pelalawan - Hairudin, Hairudin; Amir Mahmud (Bedelau: Journal of Education and Learning, 2021)
The purpose of this study was to determine the effect of job satisfaction on work discipline of the kerinci sub district head office in pelalawan district. The sample in this study were employees at Kerinci Sub District Head Office In Pelalawan District totaling 32 people. While the variables examined in this study is the job satisfaction and work discipline. Analysis of data using simple linear regression method using validity, reliability, R2 and t test. The tests are conducted to determine the relationship between the independent variables (independent variables) and dependent variable (dependent variable). Based on the results obtained that the job satisfaction simultaneously affect the work discipline of employees with a value of correlation R = 0.728 which shows the close relationship between the job satisfaction and work discipline at Kerinci Sub District Head Office In Pelalawan District. While the R-square at 0.530 which can mean job satisfaction has a contribution of 53% contribution to work discipline at Kerinci Sub District Head Office In Pelalawan District. Partially obtained job satisfaction positive and significant effect on the work discipline at Kerinci Sub District Head Office In Pelalawan District with signifivantly 0,000 smaller than alpha 0,05. With simple linear regression equation in this study : Y = 7.694 + 0.634X.